(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In response to the critical imperative for sustainable and environmentally friendly energy solutions, the global spotlight has intensified on renewable energy sources. This abstract presents a comprehensive exploration of the significance, advantages, and obstacles associated with renewable energy